The Oxford handbook of the economics of central banking - Mayes, David G., (Oxford handbooks online., 2019)
The Oxford Handbook of the Economics of Central Banking covers a wide range of central bank topics, including governance, independence, balance-sheet and crisis management, and the challenges in macroeconomic modeling. The book is intended as an up-to-date reference for the current and potential challenges faced by central banks in the conduct of monetary policy and in the search for the maintenance of financial system stability. The approach involves a wide variety of views about the past and present behavior and performance of central banks around the world, with the aim of providing a state-of-the-art perspective on the likely future challenges to be faced by this critical institution. Clearly, one of the motivations for the book is the great financial crisis of 2007-2009.